President Trump’s Declarations on Official Development Assistance: A Change of Policy? - Zaremba, Michał (International Studies. Interdisciplinary Political and Cultural Journal, 2019)
For years official development assistance (ODA) has been one of the most important forms of financial assistance provided to developing countries by highly developed countries. Despite the controversy over the effectiveness of assistance, it has become a permanent element of the international aid system. With the election of Donald Trump and one of the key slogans of his campaign – America first – the political climate around official development assistance is changing. The aim of the article is to analyze the role of official development assistance in political declarations of the current president of the United States.